Oral microbiota maturation during the first 7 years of life in relation to allergy development. Issue 10 (28th September 2018) - Dzidic, M.; Abrahamsson, T. R.; Artacho, A.; Collado, M. C.; Mira, A.; Jenmalm, M. C.
Abstract: Background: Allergic diseases have become a major public health problem in affluent societies. Microbial colonization early in life seems to be critical for instructing regulation on immune system maturation and allergy development in children. Even though the oral cavity is the first site of encounter between a majority of foreign antigens and the immune system, the influence of oral bacteria on allergy development has not yet been reported. Objective: We sought to determine the bacterial composition in longitudinally collected saliva samples during childhood in relation to allergy development. Methods: Illumina sequencing of the 16S rDNA gene was used to characterize the oral bacterial composition in saliva samples collected at 3, 6, 12, 24 months, and 7 years of age from children developing allergic symptoms and sensitization (n = 47) and children staying healthy (n = 33) up to 7 years of age. Results: Children developing allergic disease, particularly asthma, had lower diversity of salivary bacteria together with highly divergent bacterial composition at 7 years of age, showing a clearly altered oral microbiota in these individuals, likely as a consequence of an impaired immune system during infancy. Moreover, the relative amounts of several bacterial species, including increased abundance of Gemella haemolysans in children developing allergies and Lactobacillus gasseri and L. crispatus in healthy children, were distinctive during early infancy, likely influencing early immune maturation. Conclusion: Early changes in oral microbial composition seem to influence immune maturation and allergy development. Future experiments should test the probiotic potential of L. gasseri and L. crispatus isolates. Abstract : Early changes in oral microbial composition seem to influence immune maturation and allergy development. Oral microbiota increases in bacterial diversity and richness through time. By 7 years of age, allergic children have a lower diversity of salivary bacteria, as well as a highly divergent bacterial composition, compared to healthy children.